Implementasi Trilogi Jurnalisme Oleh Wartawan Dalam Peliputan Berita(Study Di Tribun Sumsel) - Rama Sutra; M Amin Sihabudin; Ahmad Harun Yahya (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2024)
The relationship between the press and journalism is closely intertwined. The press, an institution responsible for providing information to the public, while journalism is the process carried out by journalists to gather, write, and present information that will later be published by the mass media. The role of the press is crucial as they ensure that the public can access accurate, up-to date, and beneficial information. This study aims to determine the extent to which journalists from Tribun Sumsel understand and adhere to the principles of journalism in field practice, focusing on their understanding of the journalism trilogy, its implementation, and the challenges faced. The research objective is to explore how journalists apply professionalism, independence, and integrity in news coverage. The author used a qualitative descriptive method by conducting direct observations in the field and seeking information through observation and interviews as an approach in the research. The results of the implementation of the journalism trilogy by journalists from Tribun Sumsel, namely professionalism, independence, and integrity, are reflected in interviews with Tribun Sumsel journalists. Tribun Sumsel journalists emphasize the importance of seeking news with significant news value, carrying out tasks independently without being tied to any party, and upholding integrity and honesty in conveying information. Journalists from Tribun Sumsel face various challenges in carrying out their duties with professionalism, independence, and integrity. These challenges include issues of welfare, time pressure, physical security, the use of technology and social media, and obtaining reliable sources of information. In addition, they also have to strive to maintain independence from external pressures and ensure the integrity of facing temptations such as the giving of envelopes. Nevertheless, Tribun Sumsel actively addresses these challenges through regular editorial meetings to provide corrections and improvements to news, as well as by enhancing self-competence and adopting diverse confirmation approaches in coverage.